2017
DOI: 10.1109/tpwrs.2016.2628959
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Mixture Based Probabilistic Load Flow For LV-Network Planning

Abstract: Abstract-Due the many uncertainties present in the evolution of loads and distributed generation, the use of probabilistic load flow in low voltage (LV) networks is essential for the evaluation of the robustness of these networks from a planning perspective. The main challenge with the assessment of LV-networks is the sheer number of networks which need to be analysed. Moreover, most loads in the LV-network have a volatile nature and are hard to approximate using conventional probability distributions. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Nonetheless, detailed information is scarce at the LV network level, such as the particular phase where a single-end user or DER unit is connected [43], despite successful smart grid pilot projects such as Smartcity Malaga [44], INTEGRIS [5], IDE4L [45], or MONICA [46] have dedicated special efforts in distribution network digitalization and state estimation. Therefore, technical solutions are available today to address congestion in singular elements such as LV feeder phases, avoiding bottlenecks that may arise even earlier in the case of significant DER penetration or demand growth [47,48], since technical constraint violations may occur at an earlier stage [49].…”
Section: Congestion In LV Distribution Networkmentioning
confidence: 99%
“…Nonetheless, detailed information is scarce at the LV network level, such as the particular phase where a single-end user or DER unit is connected [43], despite successful smart grid pilot projects such as Smartcity Malaga [44], INTEGRIS [5], IDE4L [45], or MONICA [46] have dedicated special efforts in distribution network digitalization and state estimation. Therefore, technical solutions are available today to address congestion in singular elements such as LV feeder phases, avoiding bottlenecks that may arise even earlier in the case of significant DER penetration or demand growth [47,48], since technical constraint violations may occur at an earlier stage [49].…”
Section: Congestion In LV Distribution Networkmentioning
confidence: 99%
“…The network sensitivity S t V can be calculated based on Equations (9) and (13). Similarly, ∆V t is easily derived using Equations (15) and (16).…”
Section: Neural Network Architecturementioning
confidence: 99%
“…In this case, state prediction of the network system states will be of high value to account for the probabilistic system states that will occur in the near future. For coping with the high stochasticity of DER and end user behaviour, a probabilistic approach is required to determine potential network risks [15][16][17]. On the down side, probabilistic approaches often require some form of probabilistic power flow (PPF) calculations to evaluate the probability of having operation limit violations at certain locations in the network.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of unknown input PDF’s, a method for nonparametric probabilistic load flow analysis is developed in [5]. Other studies mainly use a Gaussian mixture model (GMM) to approximate the PDF of loads or a mix of DER’s, which cannot be approximated with a known shape PDF [6]–[8]. Furthermore, there has been tremendous effort towards real-time DSE in support of next generation power systems [14]–[23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the GMM, which is an approximate presentation of the PDF’s of NGRV’s, is utilized in the proposed estimator. As a weighted sum of several Gaussian components, GMM is widely used for NGRVs probability distribution [6]–[8], [37], [38]. More specifically, in many studies, GMM has been suggested to model the PDFs of load power and renewable energy sources [39]–[43].…”
Section: Introductionmentioning
confidence: 99%